Trading behaviour of Malaysia investor during covid-19 pandemic: speculation or value investment - Lim, Vee Kyi; Ng, Ke Long; Oi, Ching Ying; Ong, Seong Lik; Su, Vivian Zhi Chi (2022)
This research is to study the performance of portfolios based on debt to equity, price volatility and market return and identifying whether there is a switch in investors’ trading behaviour before and during the coronavirus pandemic. This research collected data from KLSE top 100 market capitalization companies during 1st January 2020 to 30th June 2020. This research separates 2 periods which are 1st January 2020 to 17th March 2020 as first quarter and 18th March 2020 to 30th June 2020 as second quarter. The portfolios consist of 4 growth portfolios which derived from the lowest 25% of top 100 market capitalization companies and another 4 value portfolios that derived from largest 25% of top 100 market capitalization companies. Both the value and growth portfolios consist of 25 companies. This research used descriptive statistic to measure and compare all the portfolios performance. For the Man-Whitney-U, the returns between one portfolio and another portfolio are significantly different or same. Based on the result, all the portfolios return are significantly difference except for portfolio based on the lowest debt to equity with portfolio based on the highest debt to equity during quarter 1 year 2020. According to the descriptive statistic, all the portfolios had a negative return in the first quarter. The lowest loss of the portfolio is the portfolio based on the lowest price volatility (value portfolio). The highest loss of the portfolio is the portfolio based on the highest price volatility (growth portfolio). In addition, all the portfolios had a positive return during second quarter. The portfolio based on the lowest price volatility (value portfolio) had a lowest return and the highest price volatility (growth portfolio) had a highest return during quarter 2.